Biomass dynamics of tree and herbaceous layer under different pruning regimes in Albizia procera Benth. based agrisilviculture system in semiarid India - Dar, Shabir Ahmad; Newaj, Ram (Indian Journal of Agroforestry, 2020)
The influence of canopy pruning on the biomass production in Albizia procera based agrisilviculture system was studied and results indicated that growth and biomass accumulation in Albizia was higher in control (unpruned trees) than 50 and 70% canopy pruning. The biomass of herbaceous layer in blackgram-mustard crop sequence was in the order of crop> weed> floor litter> root> grain whereas in greengram-wheat, it followed the order of crop> grain> weed> floor litter> root. The biomass of herbaceous layer was significantly (Pâ‰¤ 0.05) higher in 70% canopy pruning than 50% canopy pruning and control (unpruned trees). The biomass of herbaceous layer (crop, weed, floor litter and root biomass) in 70% canopy pruning was about 2 times higher than control (unpruned trees).